Dimeric Drugs - Nudelman, Abraham (Current Medicinal Chemistry, 2022)
This review intends to summarize the structures of an extensive number of symmetrical-dimeric drugs, having two monomers, linked via a bridging entity emphasizing the versatility of biologically active substances reported to possess dimeric structures. The major number of these compounds consists of anticancer agents, antibiotics/ antimicrobials, and anti-AIDS drugs. Other symmetrical-dimeric drugs include antidiabetics, antidepressants, analgesics, anti-inflammatories, drugs for the treatment of Alzheimer’s disease, anticholesterolemics, estrogenics, antioxidants, enzyme inhibitors, anti- Parkinsonians, laxatives, antiallergy compounds, cannabinoids, etc. Most of the articles reviewed do not compare the activity/potency of the dimers to that of their corresponding monomers. Only in limited cases, various suggestions have been made to justify the unexpectedly higher activity of the dimers vs. that of the corresponding monomers. These suggestions include statistical effects, the presence of dimeric receptors, binding of a dimer to two receptors simultaneously, and others. It is virtually impossible to predict which dimers will be preferable to their respective monomers, or which linking bridges will lead to the most active compounds. It is expected that the extensive variety of substances mentioned, and the assortment of their biological activities should be of interest to academic and industrial medicinal chemists.
Keywords: synergy